2021
DOI: 10.7251/qol2101023a
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Evaluation of Hospitals Sterilization by Biological and Chemical Methods

Abstract: Autoclaving is one of the methods which sterilizes medical solidwaste. This study was carried out to evaluate efficiency of autoclaves in two Shahrekord hospitals(Kashani and Hajar) in Iran by biological and chemical indicators. In this study, the performance of autoclave was studied based on biological and chemical through setting 96 tests. Variables were loading type in four groups (light, medium, semi- heavy, and heavy), location, type of hospital , and temperature-135°C, time10min features in fixed pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[ 25 ] Another study that compares operational autoclaving conditions with chemical (no Bowie & Dick) and biological indicators showed that chemical present more pass test that biological indicator, but it could change with the type of loading even when using the manufacturer settings. [ 26 ] One evidence of a loss of vacuum in our test is the uniformity of Bowie & Dick sheet after use. It represents an entrapped air (non-condensable gases) inside the chamber during a sterilization cycle.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Another study that compares operational autoclaving conditions with chemical (no Bowie & Dick) and biological indicators showed that chemical present more pass test that biological indicator, but it could change with the type of loading even when using the manufacturer settings. [ 26 ] One evidence of a loss of vacuum in our test is the uniformity of Bowie & Dick sheet after use. It represents an entrapped air (non-condensable gases) inside the chamber during a sterilization cycle.…”
Section: Discussionmentioning
confidence: 99%
“…There are three indicators that can be used to detect the efficiency of the autoclave, and they include (1) physical indicators, which are the recording of temperature and pressure by devices. ( 2) Chemical indicators are used, and color change must be detected in the chemical indicator holder that has been sterilized after exposure to high temperatures 121 °C [9]. (3) Biological indicators are considered the most reliable monitor of sterilization effectiveness and are based on microorganisms, (e.g., Bacillus stearothermophilus, Bacillus subtilis, or Geobacillus stearothermophilus) spores that are killed at the standard autoclave temperature (121 °C) because these microorganisms are more resistant to high humidity and high temperatures than other pathogenic microorganisms [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…), particular factors (e.g., complex interaction between air quality, climatic conditions, and biological specifications of viral infection), and wellbeing level of individuals (lifestyle, immune system, age, gender, etc.) (Ahmadi and Fadaei 2021;Coccia, 2020). There is an inextricable connection between meteorological variables and air pollutants (Hou and Xu, 2022).…”
Section: Introductionmentioning
confidence: 99%